Optimizing the potential of children learning in science (clis) with brain gym: review on human circulatory concepts - Yunawati Sele (Universitas Negeri Jakarta, 2019)
Learning innovation is an effort to improve the quality of learning. One form of innovation is the integration of brain gym learning techniques and various learning models, including the Children Learning in Science (CLIS) model. However, so far, there has never been a study of learning innovations through the integration of brain gym techniques with the CLIS model. This study aims at finding out the optimizing of the Children Learning in Science (CLIS) models with brain gym to empower students' human circulatory conception. This study is quasi-experimental research of pretest-posttest Nonequivalent control group design. The population of this study was the students of class XI MIA SMA Negeri 7 Kupang, which consisted of 173 students. The sample of this study were students of class XI MIA1 and XI MIA 2, which consisted of 61 students. The instrument used was a test of human circulatory conception developed by Andriani (2017). The results showed that the increase in students' human circulatory conception in CLIS learning combined with a gym is 40.61% higher than the increase in students' human circulatory conception in CLIS learning. It can be concluded that the application of brain gym can optimize Children Learning In Science (CLIS) potential in empowering students' human circulatory conception.